2017
DOI: 10.1186/s12885-017-3057-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and survival in an exhaustive French cohort of pazopanib-eligible patients with metastatic soft tissue sarcoma (STS)

Abstract: BackgroundThe French EMS study prospectively collected exhaustive data from STS patients diagnosed in the Rhone-Alpes region from 2005 to 07.MethodsThe database included diagnosis/histology, surgery, radiotherapy, systemic treatments and treatment response. Treatment patterns and outcomes of patients with metastatic disease, excluding adipocytic sarcoma and GIST were analyzed.ResultsOf 888 total patients, 145 were included based on having metastatic disease and appropriate subtypes. All patients received treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(33 reference statements)
3
5
0
Order By: Relevance
“…As might be expected, the number of lines of previous systemic therapy was a significant prognostic factor for PFS among pazopanib recipients in the PALETTE study (0–1 vs 2–4 prior lines of therapy, HR [95% CI]: 0.72 [0.53–0.99]; P = 0.04) [2]. This finding is in agreement with “real-world evidence” demonstrating that patients with aSTS exhibit a decline in mPFS with each additional line of previous therapy [14]. The randomized, phase 2 EPAZ trial (NCT01861951) demonstrated that pazopanib was noninferior to doxorubicin with respect to PFS in the first-line treatment of STS in patients more than 60 years of age [15].…”
Section: Discussionsupporting
confidence: 75%
“…As might be expected, the number of lines of previous systemic therapy was a significant prognostic factor for PFS among pazopanib recipients in the PALETTE study (0–1 vs 2–4 prior lines of therapy, HR [95% CI]: 0.72 [0.53–0.99]; P = 0.04) [2]. This finding is in agreement with “real-world evidence” demonstrating that patients with aSTS exhibit a decline in mPFS with each additional line of previous therapy [14]. The randomized, phase 2 EPAZ trial (NCT01861951) demonstrated that pazopanib was noninferior to doxorubicin with respect to PFS in the first-line treatment of STS in patients more than 60 years of age [15].…”
Section: Discussionsupporting
confidence: 75%
“…As observed in previously published observational studies of patients with advanced or metastatic STS, a high degree of treatment heterogeneity was observed across lines of therapy in this study [10,11,17,18]. In this study, 43 unique regimens were observed with 117 first-to second-line treatment sequences.…”
Section: Sarcomasupporting
confidence: 67%
“…The average age of patients with clinically advanced STS in our study was 56.1 years, and 53.2 years for localized STS patients. These figures are slightly lower than those reported by the Japanese registry (58.3) [15], the Surveillance, Epidemiology, and End Results report (SEER, 58 years) [16] and for a French cohort (61.5) [17]. Our study showed that the proportion of patients in the age category 20-40 was 18.6%; this was higher than in other solid tumors (lung, 1%; liver cancer, 2%; gastric cancer, 3%; colorectal cancer, 3%; and breast cancer, 10%).…”
Section: Discussionmentioning
confidence: 59%